Corporate Governance Policy Implementation Analysis using D. Wayne Taylor Theory. Case Study: Dental and Oral Hospital by Faculty of Dentistry Universitas Indonesia (RSKGM FKG UI) in 2019 - Putri, Yusnur Mauliana Dranie; Bashabih, Masyitoh (UI Scholars Hub, 2021)
Corporate Governance is a term that is related to the direction and control of an organization, institution, or function, to fit the goals and expectations of decision makers. This research aims to conduct an analysis of corporate governance using D. Wayne Taylor’s theory by conducting a case study at the Dental and Oral Hospital by Faculty of Dentistry Universitas Indonesia (RSKGM FKG UI). The design of this research is qulitative analysis with methods of collection data through document review and in-depth interview. The results of the research are reflected in nine principles that are recognized by six incompatible principles, two principles that are appropriate, and one principle that cannot be seen in accordance with the requirements in RSKGM FKG UI that have not supported yet. Two principles that are appropriate are: the principle of the Board-CEO Relationship and the principle of the Ownership Needs.